Comparison of Measurements of Carrier to Noise Ratios of Small-Aperture Antenna Satellite-Broadcast Reception. - Tawil Paungma; Eiji Shibuya; Tooru Kamimura; Yasushi Iituka; Yoshiaki Moriya (My University, 1995)
Since the radiation patterns in small-aperture antennas are wide, they easily affected by ambient noise sources, and so their noise temperatures tend to rise. Especially in times of rainfall, at frequencies higher than 10 GHz, the noise-power values of antennas increase simultaneously with the lowering of signal levels in proportion to rainfall intensity. Consequently, at times of intense rain, the CN ratio lowers rapidly, and this effect is larger when the noise factor of receivers is lower. From this viewpoint, in order to examine how the CN-ratio characteristics of small-aperture antennas change due to propagation state, various measurements of CN ratio, including a long-period measurement, were carried out using antennas differing in aperture and type. With these measurements the degree of the effect of antenna's noise-temperature on the increasing deterioration of CN ratios was shown quantitatively for both low noise-factor and other receivers. It was found that there are certain types of plane-type antennas in which the lowering of CN ratios due to weather-environment conditions such as rainfall, the adhesion of waterdrops, etc. was greater than in parabola-type ones.
Keywords: Aperture (computer memory); Noise temperature; Carrier-to-noise ratio; Antenna Design and Optimization